Evolutions of the complex relationship between education and territories - Barthes, Angela; Champollion, Pierre; Alpe, Yves (Science, society and new techologies series. Education set, 2018)
The book weaves the story of the complex links between education and its territories. The aim here is to examine the education couple - understood in the broadest sense: school, college, high school, universities - and territory, according to three main axes: the history and the characterization of the different ties maintained And which the school and its territory always maintain; That of the categorization and characterization of the territories in which the school is situated, of the educational policies - both explicit and grassroots - connected with it and their effects on the school; That of recent pedagogical, didactic and organizational innovations. The book is based on French specialists in territorial education issues.